2009
DOI: 10.1007/s00134-009-1471-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of shock requiring norepinephrine on the accuracy and reliability of subcutaneous continuous glucose monitoring

Abstract: Circulatory shock requiring norepinephrine therapy, as well as other covariates, had no influence on the accuracy and reliability of the CGMS in critically ill patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 35 publications
3
82
0
2
Order By: Relevance
“…While few animal studies have been done, the reliability of CGMSs in critically ill patients is an area of active research. The results to date have revealed a strong correlation between arterial reference blood glucose and better performance, compared with point-of-care devices (Corstjens et al 2006;Hoedemaekers et al 2008;Holzinger et al 2009;Brunner et al 2011). These studies pointed out that the accuracy of CGMSs becomes diminished in the hypoglycaemic range.…”
Section: Discussionmentioning
confidence: 99%
“…While few animal studies have been done, the reliability of CGMSs in critically ill patients is an area of active research. The results to date have revealed a strong correlation between arterial reference blood glucose and better performance, compared with point-of-care devices (Corstjens et al 2006;Hoedemaekers et al 2008;Holzinger et al 2009;Brunner et al 2011). These studies pointed out that the accuracy of CGMSs becomes diminished in the hypoglycaemic range.…”
Section: Discussionmentioning
confidence: 99%
“…The pinpoint of our study was not to ascertain the accuracy of current CGMS -we consider this question as being already solved by larger studies mentioned above [33][34][35][36][37][38][39][40][41] . We focused on glycaemia trends of operated patients, on identification of frequent patterns of glycaemic reaction to stress and on the determination of eventual CGM impact on glycaemic stability in individual cases.…”
Section: Hunger After the Surgerymentioning
confidence: 99%
“…Others found it useful for reducing hyperglycaemic episodes 35 . The analysis of two prospective randomized trials demonstrated clinically sufficient accuracy and safety 36,37 even in patients on vasopressors 38 . Some reject the use of subcutaneous sensors in the ICU setting 39,40 .…”
Section: Introductionmentioning
confidence: 95%
“…So far, both excellent and poor performance has been reported in ICU patients (Bridges et al,. 2010;Corstjens et al, 2006;Holzinger et al, 2009;Price et al, 2008). Until these matters are solved, continuous monitoring of interstitial glucose values should be used with caution in the ICU.…”
Section: Glucose Monitoring In the Icu Settingmentioning
confidence: 99%